Euphemism Urgency in Multicultural Education of Indonesian Schools in Malaysia - Aswan, Aswan; Santoso, Anang; Syahri, Moch. (Proceeding International Conference on Religion, Science and Education, 2024)
This article aims to provide a comprehensive overview of the significance of euphemism in multicultural education in Indonesian schools in Malaysia. A qualitative method employing a case study approach was used in this study. The findings highlight the incorporation of euphemism in multicultural education through teaching materials and spoken learning strategies. The imperative lies in establishing an inclusive educational community that embraces differences and fostering mutual respect within the school community through the use of subtle language. By integrating euphemisms into multicultural education, this article underscores the necessity of creating an educational community that prioritizes not only academic achievements, but also the development of character values that appreciate cultural diversity. Therefore, the adoption of a refined language has emerged as a pivotal factor in establishing an inclusive Indonesian school community, laying a robust foundation for understanding, tolerance, and mutual respect within the Malaysian context.